2004
DOI: 10.1186/1471-2296-5-30
|View full text |Cite
|
Sign up to set email alerts
|

Development of a questionnaire weighted scoring system to target diagnostic examinations for asthma in adults: a modelling study

Abstract: Background: Identification and treatment of unrecognised asthmatics in the community is important for improving the health of the individual and minimising cost and quality of life burden. It is not practical to offer clinical diagnostic assessment to whole communities, and a simple tool such as a questionnaire is required to identify a smaller target group. Conventional questionnaire screening methods which separate individuals into positive and negative categories have resulted in large numbers of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Six studies used multivariable logistic regression to derive their prediction models. 14,15,17,18,20,21 One study developed a decision tree. 19 Six models were derived from adults, 14,1721 and one from children.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used multivariable logistic regression to derive their prediction models. 14,15,17,18,20,21 One study developed a decision tree. 19 Six models were derived from adults, 14,1721 and one from children.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for these conflicting findings may be the investigators' use of questionnaires as screening tools for the presence of asthma. Validation studies on questionnaires have shown that a single question on the presence of wheeze or physiciandiagnosed asthma is not a highly sensitive screening tool (26,27). In contrast, we diagnosed asthma objectively by a physician at a clinic, for patients currently complaining of wheeze, using the GINA 2007 guidelines (14), without depending on self-reporting of either wheeze or physiciandiagnosed asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A consequence of attrition is biasing of samples that leads to a lack of generalisability to the target population. However, since the prevalence of asthma — upon which the pre-test probability is dependent — is the same as in previous reports, 28,29 our pre- and post-test probability is assumed to be generalisable to the diagnosis of asthma in patients with suspected symptoms of asthma. Second, our scoring system requires external validation in a different patient population.…”
Section: Discussionmentioning
confidence: 95%